Greenvolt’s IPO - Brites, Francisco Graça de Sousa (2023)
In recent years, a noticeable global trend toward the usage of sustainable practices and green energy choices has occurred. Lately the war on Ukraine and the resultant crisis on the supply of gas throughout Europe has put more pressure on the European Union to guarantee a reliable supply of gas without being dependant in Russia. The ultimate goal of the European countries is to have their own sources of energy, ideally green ones. These circumstances put companies that can provide a green answer to the energy necessity on the spotlight. Greenvolt is the biggest Portuguese figure of this event, and it has had growing media and investor interest as some similar foreign companies. Consequently, particularly the big players of this sector have been performing greatly on the financial markets as they are considered a reliable bet for the future. The aim of this dissertation is to analyse Greenvolt, its IPO and its posterior financial performance on the markets. Four interconnected goals are established for this dissertation, which will be addressed successively, to study the concepts of IPO and Green IPO; to study Greenvolt and its path to the point where the IPO was released as well as the IPO process and current state; to analyse the similarities to other Green companies’ IPOs and evaluate the financial performance in the financial markets before and after the IPO; lastly to be able to forecast the evolution on the company’s growth and profit.